IP-10 Promotes Blood–Brain Barrier Damage by Inducing Tumor Necrosis Factor Alpha Production in Japanese Encephalitis - Wang, Ke; Wang, Haili; Lou, Wenjuan; Ma, Longhuan; Li, Yunchuan; Zhang, Nan; Wang, Chong; Li, Fang; Awais, Muhammad; Cao, Shengbo; She, Ruiping; Fu, Zhen F.; et al. (Frontiers in Immunology, 2018)
Japanese encephalitis is a neuropathological disorder caused by Japanese encephalitis virus (JEV), which is characterized by severe pathological neuroinflammation and damage to the blood-brain barrier (BBB). Inflammatory cytokines/chemokines can regulate the expression of tight junction (TJ) proteins and are believed to be a leading cause of BBB disruption, but the specific mechanisms remain unclear. IP-10 is the most abundant chemokine produced in the early stage of JEV infection, but its role in BBB disruption is unknown. The administration of IP-10-neutralizing antibody ameliorated the decrease in TJ proteins and restored BBB integrity in JEV-infected mice. In vitro study showed IP-10 and JEV treatment did not directly alter the permeability of the monolayers of endothelial cells. However, IP-10 treatment promoted TNF-α production and IP-10-neutralizing antibody significantly reduced the production of TNF-α. Thus, TNF-α could be a downstream cytokine of IP-10, which decreased TJ proteins and damaged BBB integrity. Further study indicated that JEV infection can stimulate upregulation of the IP-10 receptor CXCR3 on glial cells, resulting in TNF-α production through the JNK-c-Jun signaling pathway. Consequently, TNF-α affected the expression and cellular distribution of TJs in brain microvascular endothelial cells and led to BBB damage during JEV infection. Regarding regulation of the BBB, the IP-10/TNF-α cytokine axis could be considered a potential target for the development of novel therapeutics in BBB-related neurological diseases.